2017
DOI: 10.1136/gutjnl-2016-312695
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of a nomogram and online tool to predict bowel dysfunction following restorative rectal cancer resection: the POLARS score

Abstract: The Pre-Operative LARS score (POLARS) is the first nomogram and online tool to predict bowel dysfunction severity prior to anterior resection. Colorectal surgeons, gastroenterologist and nurse specialists may use POLARS to help patients understand their risk of bowel dysfunction and to preoperatively highlight patients who may require additional postoperative support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
180
3
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(200 citation statements)
references
References 62 publications
10
180
3
7
Order By: Relevance
“…Several non-controlled studies 20,23,26 have shown an association between use of a temporary ileostomy and LARS. Only one-quarter of participants received radiotherapy, all tumours were above 5 cm and half were more than 10 cm above the anal verge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several non-controlled studies 20,23,26 have shown an association between use of a temporary ileostomy and LARS. Only one-quarter of participants received radiotherapy, all tumours were above 5 cm and half were more than 10 cm above the anal verge.…”
Section: Discussionmentioning
confidence: 99%
“…59-75) and 63 (60-70) respectively; P = 0⋅207) or the frequency (22 (21)(22)(23)(24)(25) versus 22 (20)(21)(22)(23)(24); P = 0⋅437) and dietary (16 (13-18) versus 16 (12)(13)(14)(15)(16)(17)(18); P = 0⋅939) subscales (Fig. 59-75) and 63 (60-70) respectively; P = 0⋅207) or the frequency (22 (21)(22)(23)(24)(25) versus 22 (20)(21)(22)(23)(24); P = 0⋅437) and dietary (16 (13-18) versus 16 (12)(13)(14)(15)(16)(17)(18); P = 0⋅939) subscales (Fig.…”
Section: Memorial Sloan Ketting Cancer Center Bowel Function Instrumentmentioning
confidence: 97%
See 1 more Smart Citation
“…The nomogram is a graphical statistical instrument that incorporates some variables to develop a continuous scoring system, which reflects the individual and precise risk probability. Nomograms are an important part of modern medical decision making, which has been established and validated in extensive medical applications including surgery, cancer, and myocardial infarction [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent international collaboration of UK and Danish surgeons has sought to develop a tool to predict bowel dysfunction severity prior to anterior resection. The Pre-operative LARS (POLARS) score purports to help patients understand their risk of bowel dysfunction and to preoperatively highlight patients who may require additional postoperative support [24].…”
Section: Resultsmentioning
confidence: 99%